[Boarding School in Laugar, Iceland] - Streng, Evelyn Fiedler (1975)
Photograph of a boarding school in Laugar, Iceland. Large white buildings with tall red and green roofs sit at the foot of a brown hill. A stone wall surrounds a curved street in front of the buildings, trees sat along it. A river sits along the bottom edge of the photograph. The sky above is covered in grey clouds.